2010
DOI: 10.1002/adem.200980080
|View full text |Cite
|
Sign up to set email alerts
|

HRTEM Study of the Mineral Phases in Human Cortical Bone

Abstract: Although bone minerals have been widely studied by various techniques in previous studies, crystal structures and morphology of bone minerals remained as controversy. In this study, bone minerals were extracted from human cortical bone with ethylenediamine tetraacetic acid solution (pH 7.4, ambient temperature) and examined by high‐resolution transmission electron microscopy. The results showed that the majority of bone minerals were flake‐like and a few were needle‐like. Most of flake‐like minerals were less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…In high resolution mode, it allows reaching sub-angstrom resolution [13] and therefore provides atomic details of the crystals. This increased resolution comes at the cost of the image field of view, which may not provide representative results due to the tissue heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…In high resolution mode, it allows reaching sub-angstrom resolution [13] and therefore provides atomic details of the crystals. This increased resolution comes at the cost of the image field of view, which may not provide representative results due to the tissue heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…[315] Using CR (Figure 1b) we observed that the spectrum of the synthesized apatite contained all the characteristic vibrational bands for a calcium phosphate apatite, and chemical similarity with bone mineral was seen (see also (Figure 1c), and such size is similar to that of needle-like apatite observed in human cortical bone. [23] Interplanar spacing (i.e. the d-value) in the synthesized apatite has been estimated with FFT-HRTEM as 7.85±0.39 Å (Figure 1d) that is close to the typical values recorded for synthetic hydroxyapatite.…”
Section: Characterization Of Apatitesupporting
confidence: 76%
“…It is interesting that other investigations reported that human cortical bone apatite has mainly flake-like morphology (30-100 nm length) but needle-like minerals (over 100 nm length and larger than 10 nm) were observed as well. [23] The Ca/P ratio of unsintered apatite, characterized by EDX, …”
Section: Nano-apatite Physicochemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone is a complex nano-matrix system consisting of an organic framework of mainly type-I collagen fibrils in which small inorganic prism-shaped carbonated hydroxyapatite crystals (2-50 nm) are evenly embedded [222][223][224]. Because of their chemical similarity to bone mineral, calcium phosphate ceramics are considered the most promising materials for bone replacement [82].…”
Section: Introductionmentioning
confidence: 99%